The Predictive Value of Investor Sentiment Index on the Volatility of the Malaysian Stock Market - Yacob, Nathrah; Ahmad Mahdzan, Nurul Shahnaz; Arof, Hamzah (Asian Journal of Accounting Perspectives, 2016)
Motivated by evidence that excess volatility could not be explained by the present standard value efficient market models coupled with the irrational behavioural anomaly observed in the Malaysian stock market, this study aims to construct the investors’ sentiment index. The measure is intended to test whether the excess volatility may be contributed by non-fundamental factors. The index includes five proxies: stock market turnover, the number of initial public offerings, IPO initial returns, advancer decliner’s ratio, and the widely applied consumer sentiment index. Factor analysis is employed to identify the common underlying factors from the suggested proxies to construct a composite index. The results suggest that the index is a reliable tool that is able to predict the volatility of the Malaysian Kuala Lumpur Composite Index (KLCI). These findings may be applied by practitioners to assist in making investment strategies, and, in addition, to an alternative paradigm in the asset pricing model. Keywords: Investor Sentiment, Stock Market Volatility, Behavioural Finance, Malaysian Stock Market JEL Classification: E22, F30